188k views
3 votes
For the last question this is what I meant.

For the last question this is what I meant.-example-1
User Slopapa
by
4.4k points

2 Answers

3 votes

Answer:


$\text{C) } (2)/(9) / (4)/(3) = (2)/(9) \cdot(3)/(4) $

Explanation:


$\text{A) } (2)/(9) / (3)/(4) = (2)/(9) \cdot(4)/(3) $


$\text{B) } (2)/(9) / (2)/(9) = (2)/(9) \cdot(9)/(2) $


$\text{C) } (2)/(9) / (4)/(3) = (2)/(9) \cdot(3)/(4) $


$\text{D) } (9)/(2) / (4)/(3) = (9)/(2) \cdot(3)/(4) $

Note: See reciprocal of a fraction

User Grisgram
by
4.8k points
2 votes

Answer:


\mathrm{C}

Explanation:


(2)/(9) * (3)/(4)


\mathrm{Reciprocal\:of\:(3)/(4) }


(2)/(9) / (4)/(3)

User Nishit
by
4.3k points